Circumferential full-thickness skin grafting: An excellent method for the treatment of short penile skin in adult men - Che, Kexin; Wang, Keke; Yuan, Ye; Li, Fengyong; Li, Qiang (Frontiers in Surgery, 2022)
Objective Short penile skin due to excessive circumcision is a complex condition requiring surgical care. The study aims to investigate the effect of full-thickness skin grafting (FTSG) in treating short penile skin. Methods A retrospective analysis was performed on 24 patients with insufficient penile skin. The included patients underwent full-thickness skin grafting from the scrotum and the groin region in the Genital Plastic Surgery Center between February 2014 and September 2021. Morphology of the penis, length of the penis, complication, and donor area healing status was observed by the authors. Additionally, the International Index of Erectile Function Questionnaire (IIEF-5) and the patient's evaluation of penile appearance were investigated. Results An aesthetically pleasing appearance of the penis was obtained by FTSG in 24 patients. The length of penis was improved after surgery (5.70 cm ± 1.24 cm vs. 6.05 cm ± 1.33 cm, P value < 0.05). All patients had good healing of the penile area without serious complications. Only 2 cases showed minor partial necrosis and recovered soon after proper treatment. A high patient's evaluation of penile appearance was received (4.08 ± 0.71, mean ± SD) and the scores of IIEF-5 increased significantly after surgery (18.38 ± 2.24 vs. 21.08 ± 1.79, P-value < 0.05). Conclusions FTSG from the scrotum and inguinal skin provides good aesthetic and functional results for treating short penile skin. FTSG, particularly the scrotum-derived skin graft, offers a great supplement to penile skin. It could be suggested as a promising method of treating insufficient penile skin, which meets both functional and aesthetic needs.